Cang-Ai Volatile Oil Ameliorates Depressive Behavior Induced by Chronic Stress Through IDO-Mediated Tryptophan Degradation Pathway - Zhang, Kailing; Lei, Na; Li, Meng; Li, Jijun; Li, Caijun; Shen, Yue; Guo, Peixin; Xiong, Lei; Xie, Yuhuan (Frontiers in Psychiatry, 2021)
Background: Cang-ai Volatile Oil (CAVO) is a clinically effective anti-depressant. Previous studies report that CAVO exhibits of anti-depressant and anti-inflammatory effects, and modulates activity of monoamine neurotransmitter. The current study sought to explore whether CAVO exhibits anti-depressant effects of CAVO through inhibition of inflammatory response and regulation of indoleamine 2 and 3-dioxygenase (IDO)-mediated tryptophan degradation pathway. Methods: The study established chronic unpredictable mild stress (CUMS) depression-like model using rats. Body weight and food intake of animals were determined, and open field test (OFT), forced swim test (FST) and sucrose preference test (SPT)were performed to explored the behavioral changes of animals. Expression levels of IL-6, IL-1β, TNF-α, IFN-γ, IL-4, IL-10, KYN, QUIN, Trp, KYNA, 5-HT, and 5-HIAA in the prefrontal cortex of CUMS rats were determined by ELISA. Co-localization of the microglia markers, Iba1 and IL-6 was determined by immunofluorescence. Western blotting was performed to determine the protein expression level of IDO1. Results: The findings of the current study showed that CAVO increased the body weight and food intake of rats and alleviated depression-like behaviors as shown in OFT, FST, and SPT analysis. ELISA assay showed that CAVO decreased IL-6, IL-1β, TNF-α, and IFN-γ levels and increased levels of IL-4 and IL-10 in the prefrontal cortex of CUMS rats. Analysis showed that CAVO significantly reduced KYN and QUIN levels and the ratio of KYN/ Trp, whereas it increased the levels of Trp, KYNA, 5-HT, and 5-HIAA. Immunofluorescence analysis showed that CAVO reduced the number of positive cells with co-localization of microglia markers, Iba1 and IL-6. Western blot analysis showed that CAVO decreased the protein expression level of IDO1 in rats. Conclusion: The findings show that the anti-depressant effects of CAVO are mainly attributed to inhibition of the activation of microglia and downregulation of IDO expression, thus inhibiting the kynurenine pathway and reversing the effects exerted on the 5-HT system.